1997
DOI: 10.1046/j.1365-2648.1997.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

A nursing journey through discursive praxis

Abstract: This paper argues that conceiving nursing as a form of praxis, encompasses amongst other things, the critical reflection upon one's nursing practice in order to work out and understand internal and external constructions of personal theories. This reflective examination will demonstrate the implicit knowing that nurses develop as a result of their personal, day to day practice. Highlighting this knowing and incorporating the richness of their practice experience becomes the basis for their own personal nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…The theme describes RP as a tool, which can be used in groups, although RP significantly starts off as an individual cognitive process from an experience or an emotional trigger. Warelow describes it as a dimension of an outward process, a process which takes place together with others, in contrast to RP as an agent, which has the individual inward process in focus 75 …”
Section: Resultsmentioning
confidence: 99%
“…The theme describes RP as a tool, which can be used in groups, although RP significantly starts off as an individual cognitive process from an experience or an emotional trigger. Warelow describes it as a dimension of an outward process, a process which takes place together with others, in contrast to RP as an agent, which has the individual inward process in focus 75 …”
Section: Resultsmentioning
confidence: 99%
“…Carper (1978) defined four equal patterns of knowing in nursing as empirical, ethical, aesthetic, and personal knowing. Empirical or propositional ways of knowing have, however, denigrated other forms of practice knowledge derived from experience and have become the only ‘true’ or ‘valid’ foundation for nursing (Edwards 2002; Rolfe 2000; 2002; Warelow 1997).…”
Section: Foundations Of Knowledge For Mental Health Nursing Practicementioning
confidence: 99%
“…A number of authors have supported the use of reflective praxis as the most appropriate means of learning from and for nursing practice (Holmes & Warelow 2000; Penney & Warelow 1999; Rolfe 1993; Tarlier 2005; Warelow 1997) and as a vehicle through which values or beliefs can be challenged or changed (Green 2002). Critics of reflection argue that is has no clear conceptual framework or proven evidence base (Mackintosh 1998), but these arguments have their basis in positivist knowledge constructs, which are unable to recognize realities outside of the scientific paradigm (Rolfe 2005).…”
Section: Praxismentioning
confidence: 99%
“…A number of authors have suggested that nursing can usefully be conceived as constituting a form of praxis ( Holmes 1992; Bent 1993; Holmes 1993; Rolfe 1993; Lutz et al 1997; Thorne and Hayes 1997; Warelow 1997; Penney and Warelow 1999). In this paper we explore the value of conceiving nursing as a form of praxis, undertaking some groundwork about what this may entail, and in particular trying to elucidate the part played by praxis in relation to nursing ethics.…”
mentioning
confidence: 99%
“…We may reasonably say that praxis is theory and practice in an intimate relationship, and this sounds promising as a way of describing nursing. The exact nature of that relationship is surprisingly elusive, however, and a number of interpretations are offered in the nursing literature ( Warelow 1997; Penney and Warelow 1999). Nursing has not generally been sensitive to the distinctions on which these alternatives are based, however; nor to the social‐political theories from which they have emerged ( Holmes 1992).…”
mentioning
confidence: 99%